Numeric study of geothermal borehole heat exchanger enhancement via phase change material macro encapsulation. (November 2022) - Pássaro, João; Rebola, A.; Coelho, L.; Conde, J.
Abstract: This article addresses the theoretical effect of using geothermal boreholes enhanced with macro-encapsulated phase change materials (PCM) employed with a ground sourced heat pump (GSHP). The aim being the improvement of the heat pump performance through soil temperature stabilisation, taking advantage from the PCM inherent property of changing phase at a constant temperature, that can be matched with the temperature of the surrounding soil, contributing as well to increase the energy storage capacity underground. The numeric work studied different PCM thermal parameters with regards to their influence on the overall behaviour of the heat pump, with different operation modes (On/Off and Inverter) changing the solidus and liquidus temperatures and phase change enthalpy values. The CFD results showed that, while it underperformed having 0.15% difference in the best of cases (specifically the On/Off mode), it used in the best case scenario only 30% of the stored energy in the PCM. The application of macro-encapsulation did provide a stabilising effect to the soil and heap pump operation as it was originally intended to do, helping reduce energy expenditure by the system. Significant modifications are needed in order to improve, both concerning geometry and encapsulation techniques to overcome the PCM and other materials thermal limitations. Highlights: Combination of ground heat pump with encapsulated PCM with modified double "U" array. Analysis of PCM properties influence on heat exchangers behaviour. 3D, turbulent, CFD work for the work fluid with scheduled timeframe to evaluate the heat transfer. The results showed proof of concept for thermal storage with PCMs and ground heat pumps.